Milking the data: Measuring milk off-take in extensive livestock systems. Experimental evidence from Niger. (February 2016) - Zezza, Alberto; Federighi, Giovanni; Kalilou, Amadou Adamou; Hiernaux, Pierre
Highlights: Collecting accurate milk off-take data is challenging in household surveys. Competing methods are tested in a randomized trial and compared to a benchmark. Results suggest some survey methods perform satisfactorily. Survey practitioners should consider these results when collecting recall milk data. Abstract: Milk is an important source of cash and nutrients for many households in developing countries. Yet, our understanding of the role of dairy production in livelihoods and nutritional outcomes is hindered by the lack of decent quality household survey data. Data on milk off-take for human consumption are difficult to collect in household surveys for a number of reasons which make accurate recall challenging for the respondent (continuous production and seasonality among others), introducing possibly severe biases in the computation of full household incomes and farm sales, as well as in the estimation of the contribution of livestock (specifically dairy) production to agricultural value added and the livelihoods of rural households. This paper presents results from a validation exercise implemented in Niger, where alternative survey instruments based on recall methods were administered to randomly selected households, and compared to a 12-month system of physical monitoring and recording of milk production. The results of the exercise show that reasonably accurate estimates via recall methods are possible, and provide a clear ranking of questionnaire design options that can inform future survey operations.